Covid-19 Dan Dampaknya Pada Kinerja Keuangan Perusahaan Manufaktur Di Indonesia: Analisis Rasio Profitabilitas Sebelum dan Selama Pandemic Covid-19 Di Tahun 2020 (Coopetition : Jurnal Ilmiah Manajemen, 2023)
At the end of 2019, the world was startled by the emergence of a new disease caused by the Sars CoV-2 virus, now known as Coronavirus Disease-19 (Covid-19). The manufacturing sector is one of the industries affected by the onset of Covid-19 in Indonesia. Covid-19 forced manufacturing companies to lay off employees and caused a decline in the Manufacturing Purchasing Managers Index in 2020. This research aims to analyze the financial performance of manufacturing companies in Indonesia, specifically focusing on profitability ratios before and during the Covid-19 pandemic in 2020. This study is a quantitative research type using descriptive analysis. The hypothesis testing in this research utilizes non-parametric statistical analysis techniques, employing the Wilcoxon Signed Rank Test approach with the statistical tool SPSS version 25.0. The results of the research indicate that Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) before Covid-19 in 2019 were better compared to Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) during the Covid-19 pandemic in 2020 for manufacturing companies in Indonesia.